Influence of Failure Strain of Different Aluminium Alloys on Dynamic Problems - RODRIGUEZ-MILL´AN, Marcos; VAZ-ROMERO, Alvaro; RODRIGUEZ-MARTINEZ, Jose Antonio; RUSINEK, Alexis; ARIAS, Angel (Engineering Transactions, 2014)
In this work an experimental-numerical methodology is devised for analyzing ductile fracture of two aluminum alloys under different values of stress triaxiality (0.2 ≤ η ≤ 1.2) and Lode parameter (−1 ≤ μ ≤ 0). The experiments developed include combined loading (tension-torsion) tests on same NT specimen geometry for A 5754-H111 and AA 6082-T6. Numerical analysis shows that this type of specimen exhibits uniformity stable values of stress triaxiality and Lode parameter as plastic strain develops. Experimental results can be used to compare failure strain corresponding to different stress states. Moreover, to consider the influence of stress state in failure mechanics under impact loads, perforation tests of aluminum alloys have been developed in a range of impact velocity between 120 ≤ v ≤ 500 m/s. The tests were carried out with three different shape projectiles: conical (m = 29.4 g) and two blunt ones (m = 29.4 g and m = 1.1 g). Results show the dependence on energy absorption with stress state and failure strain.